2013
DOI: 10.1557/opl.2013.143
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and Raman Spectroscopic Study of Glasses in the Al2O3-B2O3-Fe2O3-Na2O-SiO2 System

Abstract: Glasses in the Al2O3-B2O3-Fe2O3-Na2O-SiO2 system were produced at a temperature of 1150 °C, poured onto a metal plate and annealed. The nature of the structural units and their bonding in the structure were studied by infrared and Raman spectroscopic techniques. The structural network of all the glasses studied is built from major [SiO 4 ] tetrahedra with 2-3 non-bridging oxygens (NBO). Incorporation of Fe2O3 offers a destructive effect in the glass network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
1
5
0
1
Order By: Relevance
“…At the current stage of our study, we could not identify the other minor peaks. The peaks at 1247 and 1323 cm −1 were previously attributed to vibrations in BO 3 structural units in boron containing glasses [30], which is consistent with our XPS analysis. Previous reports suggest that the weak peaks around the main peaks are related to the uneven distribution of B or N vacancies owing to substitutional impurities in BN [31].…”
Section: Raman Spectroscopysupporting
confidence: 91%
“…At the current stage of our study, we could not identify the other minor peaks. The peaks at 1247 and 1323 cm −1 were previously attributed to vibrations in BO 3 structural units in boron containing glasses [30], which is consistent with our XPS analysis. Previous reports suggest that the weak peaks around the main peaks are related to the uneven distribution of B or N vacancies owing to substitutional impurities in BN [31].…”
Section: Raman Spectroscopysupporting
confidence: 91%
“…Fe2O3 and Fe 3+ ions in borosilicate glasses play a role similar to Al2O3 and Al 3+ ions by interfering conversion of III B to IV B. As a result, even at high R and K values, occurrence of Fe 3+ ions in glasses reduces fraction of B 3+ ions in tetrahedral coordination and maintains significant amount of [BO 3 ] units in the glass structure as it is seen from infrared and Raman spectroscopic data [19].…”
Section: Discussionmentioning
confidence: 89%
“…XRD and SEM characterization showed that the A1 and D1 materials were fully amorphous whereas the B1 material contained a minor content of carnegieite crystals (Na1.13Al0.75Fe0.22Si0.99O4.00) and a very low concentration of magnetite-type spinel crystals [18,19]. Due to the low content of these phases in the B1 glass their effect on Fe partitioning is negligible and the majority of Fe in the glass enters the vitreous phase similar to the A1 and D1 glasses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations